Student Perceptions About Online Learning at SMA Negeri 5 Enrekang - Saleh, Sirajuddin; Marham, Marham; Jamaluddin, Jamaluddin (Universitas Negeri Makassar, 2022)
Online learning is learning that is done without face-to-face, but through an available platform. This research is a quantitative descriptive study that aims to determine students' perceptions of online learning at SMA Negeri 5 Enrekang with a sample of 91 respondents. Data collection techniques used are observation, questionnaires (questionnaire), interviews and documentation. The data analysis technique used in this study uses the percentage formula. The results showed that students' perceptions of online learning at SMA Negeri 5 Enrekang were in the good category with a percentage level of 72.61 percent in terms of aspects of learning and evaluation materials, community, online teachers, collaboration opportunities and multimedia.